Medium- and long-chain triacylglycerols and di-unsaturated fatty acyl-palmitoyl-glycerols in Chinese human milk: Association with region during the lactation - Yu, Jiahui; Yan, Zhiyuan; Mi, Lijuan; Wang, Lei; Liu, Zhengdong; Ye, Xingwang; Jin, QingZhe; Pang, Jinzhu; Wei, Wei; Wang, Xingguo (Frontiers in Nutrition, 2022)
The triacylglycerols (TAGs) of medium- and long-chain triacylglycerols (MLCT) and di-unsaturated fatty acyl-palmitoyl-glycerols (UPU) in human milk provide better nutritional effects, and should be prioritized as crucial focuses on neonatal nutrition research. However, little has been done on the influences of the lactation stage and regional diversity on MLCT and UPU. In this study, we collected 204 human milk samples during colostrum, 1st and 4th month from the north (Baotou), central (Beijing), east (Jinan), southwest (Kunming), southeast (Shenzhen), and northwest (Xining) regions of China. There were 122 species of TAGs detected with UPLC-Q-TOF-MS, including 60 kinds of MLCT and 15 kinds of UPU. The MLCT and UPU type TAGs in human milk were ~27% and ~38%, respectively. The sum content of MLCT and UPU in human milk was stable. Compared to the regional diversity, lactation stages showed more obvious influences on MLCT and UPU composition. Moreover, a summary of TAG studies indicated that Chinese human milk showed a higher ratio of O-P-L to O-P-O than in western countries.